HUBUNGAN KECERDASAN EMOSIONAL DENGAN PENYESUAIAN DIRI PADA PEREMPUAN USIA PRAMENOPAUSE DI DENPASAR SELATAN - Darsitawati, I Gusti Ayu Putri; Budisetyani, I Gusti Ayu Putu Wulan (Jurnal Psikologi Udayana; Vol 2 No 1 (2015)DO - 10.24843/JPU.2015.v02.i01.p01, 2015)
Premenopausal-aged women are susceptible to self-adjustment problems against changes experienced such as physical and psychological changes. Emotional intelligence plays an important role in addressing various issues, especially self-adjustment problems in premenopausal-aged women. This quantitative research with the correlational approach aims to determine the relationship between emotional intelligence and self-adjustment in premenopausal-aged women in South Denpasar District.   The research samples are premenopausal-aged women in Sanur Village, South Denpasar District as many as 336 women using the one-stage cluster sampling technique. This study uses two scales of measurement namely the emotional intelligence scale and the self-adjustment scale. The emotional intelligence scale consists of 30 items with the reliability value = 0.974; and the self-adjustment scale consists of 29 items with the reliability value = 0.954. The data in this study show normal distribution with p = 0.111 for emotional intelligence and p = 0.224 for self-adjustment, and have a linear relationship (p = 0.000).   The technique for the analysis used by the researcher in this study is Pearson’s product moment correlation. The analysis shows that there is a relationship between emotional intelligence and self-adjustment (p = 0.000, p <0.05). Emotional intelligence also has a direct and positive relationship with self-adjustment, in which the value of r = 0.913; there is no negative sign, and it can be said that emotional intelligence and self-adjustment have a very strong relationship (r = 0.913).   Keywords: emotional intelligence, self-adjustment